PENERAPAN MODEL PEMBELAJARAN LAPS-HEURISTIK UNTUK MEREMEDIASI MISKONSEPSI SISWA SMP TENTANG PEMANTULAN CAHAYA - Vicsta Welya Aurelia; Stepanus Sahala Sitompul; Syukran Mursyid (Universitas Tanjungpura, 2019)
AbstractThis research aimed to overcome the students’ misconception about the reflection of light by a mirror to the learning of IPA in class IX SMP Negeri 4 Sungai Raya. The method used was the pre-experimental with one group pretest posttest design. The instruments of this research were two tiers diagnostic test that was tested to 29 students which were selected using simple random sampling technique. Based on the results of data analysis, the highest profile of the students’ misconception in pretest was that the image on a plane mirror was real (93.1%). The highest profile of the students’ misconception in posttest was that the image of objects only appeared half or partially when using the size of a plane mirror size of half the height of the object (58.62%). The average percentage decreased in the number of students that the misconception is 43.44%. McNemar test result obtained the conceptual change of the number of students who had misconception occurred significantly with an average value of χ2 hitung (12.83) > χ2 table (3.84). LAPS-Heuristic learning model is expected to be used as an alternative remediation activity in order to overcome the students’ misconception. Keywords: Remediation, Misconception, LAPS-Heuristic, and Reflection of Light by a Mirror